Health and Healthy Lifestyle Habits in Primary Education: An Analysis of Spanish Autonomous Curricular Decrees Under the Current Education Law (LOMLOE) - Olatz Arce-Larrory; Erlantz Velasco; Iker Sáez (MDPI AG, 2024)
The Spanish basic education curriculum, specifically the section on primary education, addresses global challenges and recognizes schools as essential in health education. Healthy lifestyle habits are fundamental due to their impact on health and well-being, especially in children. This study analyzes the integration of health and healthy lifestyle habits in Spanish autonomous curricular decrees using a qualitative documentary analysis and a comparative approach with a statistical/descriptive basis. The corpus includes the 17 autonomous curricular decrees derived from the Organic Law 3/2020 (LOMLOE). The data, derived from the 17 autonomous curricular decrees, were examined using lexical and grammatical analyses, then processed with Atlas.ti 23 software. The results reveal that the dimensions and categories related to health and healthy lifestyle habits focus mainly on physical aspects. In common areas or fields, physical education and knowledge of the natural, social and cultural environment are the most relevant areas for integrating health and healthy lifestyle habits into the framework in this study. However, the current curriculum proposal lacks continuity between curricular elements. In summary, this study represents a step forward in the recognition of the extent to which health and healthy lifestyle habits are established in the curriculum.